2023
DOI: 10.1002/adfm.202300502
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Fluorinated Electrolytes for High‐Performance Lithium Metal Batteries

Abstract: Lithium metal batteries (LMBs), due to their ultra‐high energy density, are attracting tremendous attentions. However, their commercial application is severely impeded by poor safety and unsatisfactory cycling stability, which are induced by lithium dendrites, side reactions, and inferior anodic stability. Electrolytes, as the indispensable and necessary components in lithium metal batteries, play a crucial role in regulating the electrochemical performance of LMBs. Recently, the fluorinated electrolytes are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 172 publications
0
18
0
Order By: Relevance
“…S11†). The reasons for these results are, on the one hand, the dense fluoride component derived from TFPO during the electrochemical reaction hindered the transport of Li ions at the interface, 20,57 while on the other hand, the gradual polymerization of TFPO decreased the electrolyte ionic conductivity, also leading to an increase in polarization voltage (Fig. S12†).…”
Section: Properties Of Fce: Better Ionic Conductivity Oxidative Stabi...mentioning
confidence: 99%
See 2 more Smart Citations
“…S11†). The reasons for these results are, on the one hand, the dense fluoride component derived from TFPO during the electrochemical reaction hindered the transport of Li ions at the interface, 20,57 while on the other hand, the gradual polymerization of TFPO decreased the electrolyte ionic conductivity, also leading to an increase in polarization voltage (Fig. S12†).…”
Section: Properties Of Fce: Better Ionic Conductivity Oxidative Stabi...mentioning
confidence: 99%
“…S16†). 20 Additionally, plating/stripping cycles were tested using the electrolytes 0.03TB-2TFPO/8DOL and 0.03TB-3TFPO/7DOL and compared to 0.03TB-TFPO/9DOL, which showed that the polarization voltage increased significantly with increasing the TFPO content during cell cycling (Fig. S17†).…”
Section: Properties Of Fce: Better Ionic Conductivity Oxidative Stabi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, dimethyl sulfoxide (DMSO) was used by Cao et al to investigate its effects on ZIBs. As schematically shown in figure 5(g), the addition of DMSO not only interrupted the original H-bonds in water, but also appeared in the primary sheath of Zn 2+ , resulting into SEI with abundant Zn 12 (SO 4 ) 3 Cl 3 (OH) 15 • 5H 2 O, ZnSO 3 , and ZnS. As a result, the ZnCl 2 −H 2 O−DMSO hybrid electrolyte endowed Zn||Ti cells with a high CE of 99.5% for 400 h, and Zn||MnO2 cells a high capacity retentions of 95.3% after 500 cycles [56].…”
Section: Organic Solventsmentioning
confidence: 99%
“…Electrolytes, as the media to transport Zn 2+ and directly contact with both anode and cathode, not only have a crucial effect on electrochemical kinetics, but also play a key role in broadening the electrochemical stable potential windows (ESPWs), suppression of zinc dendrites and corrosions, and inhabitation of water decomposition and side reactions, highly affecting the overall electrochemical performance, including energy/power density and cycling life of ZIBs [13][14][15]. Moreover, compared with other strategies such as designing electrodes, current collectors, and artificial electrode-electrolyte interphases with sophisticated structures or components, electrolyte engineering is facile and easy for industrial application.…”
Section: Introductionmentioning
confidence: 99%